(untitled) (Nordic Journal of African Studies, 2002)
It would be quite naive to say that Swahili poets have never dealt with the subject of ’love’ ’sex’ and ’obscenity’. In the past however, they composed poems of such themes with a bit of obscurity if not complete opacity. This is true of taarab lyrics which, as a rule specialise in themes of ’love’ and sometimes ’sex’ and ’obscenity’. But from the 1980s, influenced by mediated global culture(s), taarab has gone fully commercial, targeting a segment of the society interested in dance, booze and sex. The taarab lyric has therefore shifted dramatically to incorporate both these elements. Things that were once upon a time considered to ’taboo’ to be articulated openly, have now gone to the public domain with accentuation. This article aims at showing structural and functional mechanism of the taarab lyric and changes that take place vis a vis change of functions, especially the commercial function which demands bluntness in expressing sex and obscenity.